DETERMINANTS OF AUDIT REPORT LAG IN STATE-OWNED ENTERPRISES - Vindi Septatiara; Made Dudy Satyawan Satyawan (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2023)
Problems related to delays in the publication of financial reports from year to year are still found in several companies listed on the Indonesia Stock Exchange (IDX). This research aims to determine the determinants or influences of profitability, financial distress, public accounting firm reputation, and audit opinion on audit report lag. The population used in this study are State-Owned Enterprises (SOE) companies listed on the IDX for the 2012-2021 period. The sampling technique used was purposive sampling and the research analysis used multiple linear regression analysis. The conclusions of data testing using SPSS version 23 show that profitability and financial distress affect audit report lag, in contrast the public accounting firm reputation and audit opinion does not affect audit report lag.